Device and method for testing local trace element pollution on surface of quartz glass part
By designing a test device for quartz glass parts, the problem of local trace element contamination in the prior art cannot be accurately detected on the surface of quartz glass parts, and accurate detection of local areas and efficient sampling solution recovery are achieved.
Patent Information
- Application Number
- CN202411596060.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-11
- Publication Date
- 2025-02-18
Smart Images

Figure CN119470609A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of quartz product detection, and more specifically, to a testing device and a testing method based on local trace element contamination on the surface of a quartz glass component. Background Art
[0002] Due to its excellent physical and chemical properties, quartz glass materials have been widely used in high-tech fields such as semiconductor manufacturing, aerospace, and optical communications. Especially in the semiconductor field, quartz glass components are indispensable key materials in chip manufacturing equipment. With the continuous reduction of chip manufacturing processes, the requirements for quartz glass components, especially the requirements for surface cleanliness, are gradually increasing. Even extremely small amounts of elemental contamination on the surface of quartz glass may have a serious impact on the quality of the product, and thus affect the stability and operating efficiency of the entire system. Therefore, the ability to accurately and quickly detect trace element contamination on the surface of quartz components has become an important demand and technical challenge in the industry.
[0003] Inductively coupled plasma mass spectrometry (ICP-MS) is one of the most direct and accurate methods for measuring trace elements. It has ppt-level detection capability and resolution and is widely used in materials research, manufacturing and testing.
[0004] At present, based on element analysis equipment such as ICP-MS, the main test methods for element contamination on the surface of quartz glass components include overall immersion method, cotton swab sampling method and direct solution collection method.
[0005] Among them, the overall immersion method is to immerse the quartz glass component as a whole in the sampling solution, take it out at regular intervals, and then test the element content in the sampling solution to obtain the element contamination on the surface of the quartz glass component. The cotton swab wiping sampling method is to dip a cleaned dust-free polyester fiber cotton swab into the sampling solution and wipe the surface of the component to be tested for sampling, then soak the cotton swab in electronic grade water and test the soaking solution to obtain the element content, such as a test method for trace ion contamination on the surface of semiconductor manufacturing equipment components with publication number CN115792080A. The direct solution collection method is to drop a known volume of solution on a specific position on the surface of the quartz glass, and collect the solution again at regular intervals for testing.
[0006] However, some of the above-mentioned test methods have certain limitations. For example, the overall immersion method can only provide data on the overall surface contamination of the component, and cannot accurately analyze local contamination; the area of the wiped area in the cotton swab sampling method cannot be accurately measured, and the sampling solution dipped by the cotton swab cannot be completely recovered, resulting in a decrease in test accuracy; in the direct solution collection method, the sampling solution may diffuse when dropped on the surface of the quartz glass, and it is also impossible to accurately test the sampling area and recover the sampling solution. Summary of the invention
[0007] The main purpose of the present invention is to provide a testing device and a testing method based on local trace element contamination on the surface of a quartz glass component, so as to solve the technical problems mentioned in the background technology.
[0008] In order to solve the above technical problems, on the one hand, the present invention proposes a testing device based on local trace element contamination on the surface of a quartz glass component, comprising:
[0009] Stage;
[0010] The quartz glass component sample to be tested is fixed on a stage, and the stage is provided with at least one sampling hole leading to the surface of the quartz glass component sample to be tested.
[0011] In the above technical solution, further, the loading platform includes: two detachably connected clamping plates;
[0012] The quartz glass component sample to be tested is installed between two clamping plates and is restricted from moving; the sampling hole is located on one of the clamping plates.
[0013] In this technical solution, the quartz glass component sample to be tested is mounted on the stage by adopting a clamping-like manner to facilitate the operation of the test personnel.
[0014] In any of the above technical solutions, further, through holes are provided on the two clamping plates; and the stage further comprises:
[0015] The connecting piece fixes the two splints through the through holes.
[0016] In the technical solution, it is convenient to combine or separate the two splints.
[0017] In any of the above technical solutions, further, the test equipment also includes:
[0018] The sealing ring is arranged on the inner port of the sampling hole and is used to seal the sampling hole and the surface of the quartz glass component sample to be tested.
[0019] In the technical solution, the sealing ring is used to seal the sampling hole, thereby preventing the sampling solution from diffusing on the sample, which would make the area of the sampling region difficult to measure.
[0020] On the other hand, a test method based on local trace element contamination on the surface of quartz glass components is also proposed. The test method steps are as follows:
[0021] S1. Place the quartz glass component sample to be tested on the testing device;
[0022] S2, adding a sampling solution of volume V1 into the sampling hole on the test device, and after a certain period of time, recovering the sampling solution from the sampling hole to finally obtain a solution to be tested of volume V2;
[0023] S3. Using the test solution in the ICP-MS test bottle, obtain the local surface trace element content of the quartz glass component.
[0024] In this technical solution, it is possible to accurately detect specific areas of the quartz glass component, thus overcoming the defect that the overall immersion method cannot provide local contamination data.
[0025] In the above technical solution, further, in step S2, the sampling solution is recovered by a dilution method.
[0026] In the present technical solution, the complete recovery of the sampling solution is achieved, the error caused by the loss of the sampling solution is reduced, and the reliability of the detection result is improved.
[0027] In any of the above technical solutions, further, all instruments used for testing need to be cleaned to remove impurities on the surface.
[0028] In this technical solution, after cleaning, contamination by impurities introduced by the instrument can be effectively avoided, and the actual situation of the sample can be more truly reflected.
[0029] In any of the above technical solutions, further, the cleaning method is: using nitric acid, hydrochloric acid or other acid solution as a soaking solution, soaking in the soaking solution for more than 12 hours, and then ultrasonically cleaning with ultrapure water for multiple times.
[0030] In this technical solution, the cleanliness of the device is improved.
[0031] In any of the above technical solutions, further, the test elements include but are not limited to metal and non-metal elements such as Li, Na, Al, K, Cr, Mn, Cu, Zr, and Pb.
[0032] In any of the above technical solutions, further, the calculation method of the trace element content on the local surface of the quartz glass component is as follows:
[0033]
[0034] The unit of surface element contamination concentration is atoms / cm 2 ;
[0035] ρ1 is the concentration of the element in the solution to be tested, in ppt;
[0036] ρ0 is the element concentration in the blank solution, in ppt;
[0037] V2 is the volume of the solution to be tested, in mL;
[0038] N A is Avogadro's constant, 6.022×10 23 ;
[0039] M is the relative atomic mass of the element;
[0040] S is the area of the sampling hole, in cm 2 .
[0041] Beneficial effects: Compared with the existing technology,
[0042] 1. The present invention can accurately detect specific areas of quartz glass components, overcoming the defect that the overall immersion method cannot provide local contamination data, and is suitable for most quartz components that only need to detect local contamination;
[0043] 2. The present invention can accurately obtain the sampling area of the sample surface, eliminates the factor that the sampling area is difficult to control in the cotton swab wiping method or the direct sampling method, and improves the test accuracy. BRIEF DESCRIPTION OF THE DRAWINGS
[0044] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0045] Figure 1 It is a three-dimensional structural schematic diagram of the test equipment of the present invention;
[0046] Figure 2 It is a schematic diagram of the internal structure of the test equipment of the present invention;
[0047] Figure 3 It is a schematic diagram of the structure of adding a sampling liquid onto a stage of the present invention;
[0048] Figure 4 It is a schematic diagram of the structure of recovering the sampling liquid on the stage of the present invention.
[0049] The following are the descriptions of the reference numerals:
[0050] 100. Quartz glass component sample; 1. Stage; 11. Clamp; 111. Sampling hole; 12. Connector; 2. Sealing ring. DETAILED DESCRIPTION
[0051] Below, the example embodiments according to the present application will be described in detail with reference to the accompanying drawings. Obviously, the described embodiments are only part of the embodiments of the present application, rather than all the embodiments of the present application, and it should be understood that the present application is not limited to the example embodiments described herein. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0052] It should be noted that, as shown in this application and claims, unless the context clearly indicates an exception, the words "a", "an", "a kind" and / or "the" do not specifically refer to the singular, but may also include the plural. Generally speaking, the terms "include" and "comprise" only indicate the inclusion of clearly identified steps and elements, and these steps and elements do not constitute an exclusive list, and the method or device may also include other steps or elements.
[0053] If the embodiments of the present invention involve directional indications (such as up, down, left, right, front, back, etc.), the directional indications are only used to explain the relative position relationship, movement status, etc. between the components under a certain specific posture (as shown in the accompanying drawings). If the specific posture changes, the directional indication will also change accordingly.
[0054] In the present invention, unless otherwise clearly specified and limited, the terms "connection", "fixation", etc. should be understood in a broad sense. For example, "fixation" can be a fixed connection, a detachable connection, or an integral connection; it can be a mechanical connection or an electrical connection; it can be a direct connection or an indirect connection through an intermediate medium, it can be the internal connection of two elements or the interaction relationship between two elements, unless otherwise clearly defined. For ordinary technicians in this field, the specific meanings of the above terms in the present invention can be understood according to specific circumstances.
[0055] In addition, if there are descriptions involving "first", "second", etc. in the embodiments of the present invention, the descriptions of "first", "second", etc. are only used for descriptive purposes and cannot be understood as indicating or implying their relative importance or implicitly indicating the number of technical features indicated. Therefore, the features defined as "first" and "second" may explicitly or implicitly include at least one of the features. In addition, the meaning of "and / or" appearing in the full text includes three parallel schemes. Taking "A and / or B" as an example, it includes scheme A, or scheme B, or a scheme that satisfies both A and B. In addition, the technical solutions between the various embodiments can be combined with each other, but it must be based on the ability of ordinary technicians in the field to implement. When the combination of technical solutions is contradictory or cannot be implemented, it should be deemed that such a combination of technical solutions does not exist and is not within the scope of protection required by the present invention.
[0056] In order to overcome the defects of the prior art, the present application proposes a test method based on local trace element contamination on the surface of a quartz glass component, that is, by fixing a completely cleaned acid corrosion test device on the surface of a quartz glass component, the sampling solution can be completely confined to a target sampling area with a certain area. This method can accurately obtain the area of the sampling area, and can also conveniently achieve complete recovery of the sampling solution, and then test the element content in the sampling solution by ICP-MS. This method can effectively improve the accuracy and comparability of the trace element content on the surface of the quartz glass component, which plays an important role in the application of the quartz glass component.
[0057] The test method for local trace element contamination on the surface of a quartz glass component of the present application is described in detail below through the following examples.
[0058] A test method based on local trace element contamination on the surface of quartz glass components, the test method steps are as follows:
[0059] S1. placing a quartz glass component sample to be tested on a testing device, wherein the testing device has a sampling hole leading to a predetermined sampling area on the surface of the quartz glass component sample;
[0060] S2, adding a sampling solution of volume V1 into the sampling hole, and after a certain period of time, recovering the sampling solution from the sampling hole to finally obtain a solution to be tested of volume V2;
[0061] S3. Using the test solution in the ICP-MS test bottle, obtain the local surface trace element content of the quartz glass component.
[0062] This method can accurately sample a local area on the surface of a quartz glass component by designing a test device with a sampling hole of a predetermined sampling area. This solves the limitation that the overall immersion method cannot provide local contamination information, making the test results more precise and targeted.
[0063] By directly adding a predetermined volume of sampling solution into the sampling hole and recovering it, the accuracy and repeatability of the sampling process are ensured. In contrast, the wiping area in the cotton swab sampling method is difficult to accurately control, and the sampling solution is not completely recovered, which can easily lead to a decrease in test accuracy.
[0064] Since the sampling hole is designed with adjustable position and size as needed, this method can be flexibly applied to quartz glass parts with different shapes, sizes and surface properties, and has wide applicability.
[0065] It should be noted that in step S1, all the instruments used for the test need to be cleaned to remove impurities on the surface. After cleaning, the impurity contamination introduced by the instruments can be effectively avoided, and the actual situation of the sample can be more truly reflected.
[0066] Specifically, the cleaning method is: use nitric acid, hydrochloric acid or other acid solutions as soaking liquid, then soak in the soaking liquid for more than 12 hours, and then use ultrapure water for ultrasonic cleaning multiple times to achieve the purpose of removing all additional metal impurities. Nitric acid, hydrochloric acid or other acid solutions are used as soaking liquids. These acid solutions are highly corrosive and can effectively remove metal oxides, inorganic salts, organic matter and other impurities on the surface of the equipment. Soaking for more than 12 hours ensures that the impurities react fully with the acid solution, thereby achieving a deep cleaning effect. Ultrapure water is then used for ultrasonic cleaning. The cavitation effect of ultrasound can produce a large number of tiny bubbles in the water. These bubbles will produce strong shock waves when they burst, thereby peeling off and taking away the residual impurities and cleaning liquid on the surface of the equipment. The cleanliness of the surface of the equipment is further ensured by multiple cleanings.
[0067] It should be noted that in step S2, the sampling solution is recovered by dilution, which can achieve complete recovery of the sampling solution, high collection efficiency, reduce the error caused by the loss of the sampling solution, and thus improve the reliability of the detection result.
[0068] It should be noted that the test elements include but are not limited to metal and non-metal elements such as Li, Na, Al, K, Cr, Mn, Cu, Zr, and Pb.
[0069] The calculation method of trace element content on the local surface of quartz glass components is as follows:
[0070]
[0071] The unit of surface element contamination concentration is atoms / cm 2 ;
[0072] ρ1 is the concentration of the element in the solution to be tested, in ppt;
[0073] ρ0 is the element concentration in the blank solution, in ppt;
[0074] V2 is the volume of the solution to be tested, in mL;
[0075] N A is Avogadro's constant, 6.022×10 23 ;
[0076] M is the relative atomic mass of the element;
[0077] S is the area of the sampling hole, in cm 2 .
[0078] like Figure 1-Figure 4As shown, in the technical solution, the testing device in step S1 includes: a stage 1, on which a quartz glass component sample 100 to be tested is fixed, and on which at least one sampling hole 111 leading to the surface of the quartz glass component sample 100 to be tested is provided; and a sealing ring 2, which is provided on the inner end of the sampling hole 111 and is used to seal and connect the sampling hole 111 with the surface of the quartz glass component sample 100 to be tested.
[0079] Since the inner diameter of the sampling hole 111 is designed according to actual conditions, its inner diameter is known. Therefore, after a certain amount of sampling solution is dripped into the sampling hole, the area of the local area on the surface of the quartz glass component 100 to be detected can be accurately known. Then, by recovering the sampling solution and then testing it through ICP-MS, the content of trace elements on the local surface of the quartz glass component sample 100 can be accurately detected.
[0080] In the present technical solution, the stage 1 comprises: two detachably connected clamping plates 11 ; wherein the quartz glass component sample 100 to be tested is installed between the two clamping plates 11 and is restricted from moving; and the sampling hole 111 is located on one of the clamping plates 11 .
[0081] The quartz glass component sample 100 to be tested is mounted on the stage 1 in a similar clamping manner to facilitate the operation of the test personnel.
[0082] Specifically, the two clamps 11 can be combined or separated by the connecting member 12. The connecting member 12 can be a clamp for clamping the two clamps 11. More conveniently, bolts and nuts can be used for fixing. That is, through holes are opened on the two clamps 11, and the connecting member 12 is a bolt and nut installed on the through hole.
[0083] It should be noted that the clamping plate 11 is made of polytetrafluoroethylene material.
[0084] Embodiment 1:
[0085] This embodiment describes the sampling and testing process for testing the impurity elements on the surface of a quartz glass component sample using the above method.
[0086] Step 1: Cleaning of equipment
[0087] The splints, sealing rings, connectors, volumetric flasks and other instruments used in the test were soaked in 10% electronic grade nitric acid solution for more than 12 hours in advance, cleaned more than 8 times with ultrapure water (resistivity > 18MΩ) before use, and blown dry with high-purity nitrogen.
[0088] Step 2: Sampling
[0089] 2.1. Open the sample package of the quartz glass component to be tested on the clean bench in the Class 100 clean room, and then use bolts to fix the polytetrafluoroethylene splint on the sample. During this period, ensure that the sealing ring fits well with the sample surface and the sampling hole;
[0090] 2.2. Add 1 mL of 1% nitric acid solution to the sampling hole, let it stand for 5 minutes, and then aspirate and recover it into a volumetric flask;
[0091] 2.3. Rinse the sample surface in the sampling hole with 1% nitric acid solution, and recover the rinse solution into the volumetric flask in step 2.2. Repeat the operation several times to ensure complete recovery of the metal elements.
[0092] 2.4. Shake the volumetric flask to the required volume to obtain the solution to be tested;
[0093] 2.5. The blank control solution is 1% nitric acid solution.
[0094] Step 3: Testing and result calculation
[0095] 3.1. Use ICP-MS to test the concentration of metal elements in the test solution and blank solution;
[0096] 3.2. Test elements include Li, Na, Al, K, Cr, Mn, Cu, Zr, Pb, etc.
[0097] 3.3. Use the following formula to calculate the surface element contamination concentration.
[0098]
[0099] The unit of surface element contamination concentration is atoms / cm 2 ;
[0100] ρ1 is the concentration of the element in the solution to be tested, in ppt;
[0101] ρ0 is the element concentration in the blank solution, in ppt;
[0102] V2 is the volume of the solution to be tested, in mL;
[0103] N A is Avogadro's constant, 6.022×10 23 ;
[0104] M is the relative atomic mass of the element;
[0105] S is the area of the sampling hole, in cm 2 .
[0106] Step 4. Test results
[0107] The following table summarizes the test results
[0108] Metallic elements Test Results unit Li 7 23.31 <![CDATA[10 10 atoms / cm 2 ]]> Na 23 190.48 <![CDATA[10 10 atoms / cm 2 ]]> Al 27 841.49 <![CDATA[10 10 atoms / cm 2 ]]> K 39 156.91 <![CDATA[10 10 atoms / cm 2 ]]> Cr 52 18.01 <![CDATA[10 10 atoms / cm 2 ]]> Mn55 83.89 <![CDATA[10 10 atoms / cm 2 ]]> Cu 63 35.97 <![CDATA[10 10 atoms / cm 2 ]]> Zr 90 92.10 <![CDATA[10 10 atoms / cm 2 ]]> Pb 208 5.58 <![CDATA[10 10 atoms / cm 2 ]]>
[0109] Table 1
[0110] Comparative Example 1
[0111] This comparative example describes the sampling and testing process for testing impurity elements on the surface of a quartz glass sample using a cotton swab to recover the solution.
[0112] Step 1: Cleaning of equipment
[0113] The volumetric flasks and HDPE bottles used in the test were soaked in 10% electronic grade nitric acid solution for more than 12 hours in advance, cleaned more than 8 times with ultrapure water (resistivity > 18MΩ) before use, and blown dry with high-purity nitrogen.
[0114] Step 2: Sampling
[0115] 2.1. Open the packaging of the quartz glass component samples to be tested on the clean bench in a Class 100 clean room;
[0116] 2.2. Use a pipette to take 1 mL of 1% nitric acid solution and drop it on the sample surface. Use the pipette tip to divide the solution into a regular rectangular area and mark it.
[0117] 2.3. After 5 minutes of sampling, use multiple polyurethane cotton swabs to completely absorb the solution and place it in a HDPE bottle;
[0118] 2.4. Soak the cotton swab in 1% nitric acid solution and rinse it repeatedly for 5 times. Transfer all the solution in the HDPE bottle to a 10mL volumetric flask, dilute to volume and shake well to obtain the solution to be tested.
[0119] 2.5. For the blank control solution, soak and rinse the same number of blank cotton swabs with 1% nitric acid solution, transfer them to a 10 mL volumetric flask, and shake to volume.
[0120] Step 3: Testing and result calculation
[0121] 3.1 Use ICP-MS to test the concentration of metal elements in the test solution and blank solution
[0122] 3.2 Test elements are Li, Na, Al, K, Cr, Mn, Cu, Zr, Pb, etc.
[0123] 3.3 Use a vernier caliper to measure the size of the sampling area and calculate the area
[0124] 3.4 Calculate the surface element concentration using formula (1)
[0125] Step 4. Test results
[0126] The following table summarizes the test results
[0127] Metallic elements Test Results unit Li 7 <0 <![CDATA[10 10 atoms / cm 2 ]]> Na 23 <0 <![CDATA[10 10 atoms / cm 2 ]]> Al 27 36.01 <![CDATA[10 10 atoms / cm 2 ]]> K 39 <0 <![CDATA[10 10 atoms / cm 2 ]]> Cr 52 <0 <![CDATA[10 10 atoms / cm 2 ]]> Mn55 0.84 <![CDATA[10 10 atoms / cm 2 ]]> Cu 63 9.03 <![CDATA[10 10 atoms / cm 2 ]]> Zr 90 <0 <![CDATA[10 10 atoms / cm 2 ]]> Pb 208 0.25 <![CDATA[10 10 atoms / cm 2 ]]>
[0128] Table 2
[0129] From the test results of Example 1 and Comparative Example 1, it can be seen that the test results of multiple elements in Table 2 are less than 0, which is because the element concentration in the test solution is lower than that in the blank control group. This phenomenon shows that the use of polyurethane cotton swabs introduces impurities, which greatly affects the test.
[0130] Therefore, the method provided in the present application can effectively avoid impurity contamination introduced by the sampling device, fully recover the test solution, and can conveniently calculate the sampling area, greatly improving the accuracy, reliability and repeatability of the test.
[0131] The embodiments of the present disclosure have been described above, and the above description is exemplary, not exhaustive, and is not limited to the disclosed embodiments. Many modifications and changes will be apparent to those of ordinary skill in the art without departing from the scope and spirit of the described embodiments. The selection of terms used herein is intended to best explain the principles of the embodiments, practical applications, or improvements to the technology in the market, or to enable other persons of ordinary skill in the art to understand the embodiments disclosed herein.
Claims
1. A testing device for local trace element contamination on the surface of a quartz glass component, characterized in that: include: Stage (1); The quartz glass component sample (100) to be tested is fixed on the stage (1), and the stage (1) is provided with at least one sampling hole (111) leading to the surface of the quartz glass component sample (100) to be tested.
2. The testing device for local trace element contamination on the surface of a quartz glass component according to claim 1, characterized in that: The object carrier (1) comprises: Two detachably connected splints (11); The quartz glass component sample (100) to be tested is installed between two clamping plates (11) and is restricted from moving; the sampling hole (111) is located on one of the clamping plates (11).
3. The testing device for local trace element contamination on the surface of a quartz glass component according to claim 2, characterized in that: Through holes are provided on the two clamping plates (11); the loading platform (1) also includes: A connecting piece (12) is used to fix the two clamping plates (11) via the through hole.
4. The testing device for local trace element contamination on the surface of a quartz glass component according to any one of claims 1 to 3, characterized in that: The testing device also includes: A sealing ring (2) is arranged on the inner end of the sampling hole (111) and is used to seal the sampling hole (111) and the surface of the quartz glass component sample (100) to be tested.
5. A method for testing local trace element contamination on the surface of a quartz glass component, characterized in that: The test method steps are as follows: S1. Place the quartz glass component sample to be tested on the testing device; S2, adding a sampling solution of volume V1 into the sampling hole on the test device, and after a certain period of time, recovering the sampling solution from the sampling hole to finally obtain a solution to be tested of volume V2; S3, using the test solution in the ICP-MS test bottle to obtain the local surface trace element content of the quartz glass component; Wherein, the testing device used in step S1 is the testing device of any one of claims 1-4.
6. The method for testing local trace element contamination on the surface of a quartz glass component according to claim 5, characterized in that: In step S2, the sampling solution is recovered by dilution method.
7. The method for testing local trace element contamination on the surface of a quartz glass component according to claim 5, characterized in that: All instruments used in the test need to be cleaned to remove surface impurities.
8. The method for testing local trace element contamination on the surface of a quartz glass component according to claim 7, characterized in that: The cleaning method is: use nitric acid, hydrochloric acid or other acid solution as the soaking solution, soak in the soaking solution for more than 12 hours, and then use ultrapure water ultrasonic cleaning for multiple times.
9. The method for testing local trace element contamination on the surface of a quartz glass component according to claim 5, characterized in that: Test elements include but are not limited to metal and non-metal elements such as Li, Na, Al, K, Cr, Mn, Cu, Zr, and Pb.
10. The method for testing local trace element contamination on the surface of a quartz glass component according to claim 5, characterized in that: The calculation method of trace element content on the local surface of quartz glass components is as follows: The unit of surface element contamination concentration is atoms / cm 2 ; ρ1 is the concentration of the element in the solution to be tested, in ppt; ρ0 is the element concentration in the blank solution, in ppt; V2 is the volume of the solution to be tested, in mL; N A is Avogadro's constant, 6.022×10 23 ; M is the relative atomic mass of the element; S is the area of the sampling hole, in cm 2 .
Citation Information
Patent Citations
Method for testing trace ion pollution on surface of semiconductor manufacturing equipment component
CN115792080A
Cited By
Nondestructive testing method for local residual cerium dioxide on surface of quartz glass product
CN120971549A